2018
DOI: 10.3382/ps/pex284
|View full text |Cite
|
Sign up to set email alerts
|

Meat quality traits and proteome profile of woody broiler breast (pectoralis major) meat

Abstract: Woody breast meat has recently become prevalent in the broiler industry in both the United States and European Union. Recent publications have described the meat quality characteristics of woody breast meat as having hardened areas and pale ridge-like bulges at both the caudal and cranial regions of the breast. The present study investigated the meat quality (pH, color, cooking loss, and shear force) and protein quality characteristics (protein and salt-soluble protein content) in woody breast meat as compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
68
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 48 publications
13
68
1
Order By: Relevance
“…The significant effect of bleeding on meat colour was showed by Hopkins et al (2006). Additionally, Cai et al (2018) showed significantly lower a* value of breast meat in normal meat with comparison to wooden breast. They observed that normal meat was significantly less red than other faulty breast meat (wooden breast and white stripping).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The significant effect of bleeding on meat colour was showed by Hopkins et al (2006). Additionally, Cai et al (2018) showed significantly lower a* value of breast meat in normal meat with comparison to wooden breast. They observed that normal meat was significantly less red than other faulty breast meat (wooden breast and white stripping).…”
Section: Resultsmentioning
confidence: 88%
“…One of the negative factors is the high density of birds, which makes them very stressed. Secondly, fast muscle growth causes weakening of bones (the head of the tibia) and the formation of a series of muscle myopathies, such as white striping, wooden breast, spaghetti meat and deep pectoral myopathy (Cai et al, 2018). In addition, because of the high density of birds Sałek, P., Przybylski, W., Jaworska, D., Adamczak, L., Zielińska, D., Głuchowski, A.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings have been observed in chicken breast with WB myopathy (with or without WS). Several authors have reported consistent results including significant reduction in protein and ash contents and increase in moisture and lipid levels in WB muscles compared to their normal counterpart (Cai et al., ; Soglia et al., ,b; Wold et al., ). The collagen content in the WB, SM, WB, WS/WB, and WS/SM presented contrasting results since some studies showed a higher content than the normal group and others did not observe a significant difference (Baldi et al., ; Cai et al., ; Soglia et al., ,b).…”
Section: Physicochemical and Histological Properties Of Wb Ws And Smmentioning
confidence: 74%
“…The drip loss was determined according to Liu et al [72]. Cooking loss was measured according to the protocol described by Cai et al [73]. The pH values of the pectoral muscle at 45 minutes and 24 hours were measured by a pH meter (testo 205; Germany).…”
Section: Meat Quality Analysismentioning
confidence: 99%